2017
DOI: 10.21037/jtd.2017.06.124
|View full text |Cite
|
Sign up to set email alerts
|

Standardized uptake value and radiological density attenuation as predictive and prognostic factors in patients with solitary pulmonary nodules: our experience on 1,592 patients

Abstract: was considered for the evaluation of nodules, the maximum standardized uptake value (SUVmax) more than 2.5 is used frequently as a cut off for malignancy. The purpose of this study is to evaluate SUVmax PET/CT and pulmonary attenuation patterns at MSCT in patients with SPN according to morphological and pathological characteristics of the lesion.Methods: A retrospective study on 1,592 SPN patients was carried out following approval by the Italian Registry of VATS Lobectomies.Results: All patients underwent VAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
(17 reference statements)
1
10
0
Order By: Relevance
“…However, no significant difference was found amongst the malignant histopathologic subtypes. Also, Divisi et al (12) found no significant correlation between histopathological findings and SUV max (p=0.586). Davidson et al (26) showed that SCC was more 18 F-FDG avid than adenocarcinoma.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, no significant difference was found amongst the malignant histopathologic subtypes. Also, Divisi et al (12) found no significant correlation between histopathological findings and SUV max (p=0.586). Davidson et al (26) showed that SCC was more 18 F-FDG avid than adenocarcinoma.…”
Section: Discussionmentioning
confidence: 94%
“…However, 18 F-FDG avidity can also be observed in benign conditions such as inflammation, infection; or malignant diseases can be less avid secondary to volumetric effects such as nodule size, ROI placement, etc. (12,13,14,15,16,17,18,19). SUV max values of half of the bronchoalveolar carcinoma and carcinoid tumors which constitute 2% of all lung cancers, may cause false negative PET results (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if surgery is performed at an early stage of the disease, there is still a 25–50% recurrence rate . Solitary pulmonary nodules (SPNs) are single, well‐defined lesions of a diameter of ≤ 3 cm that are completely surrounded by gas‐containing lung tissue, without pulmonary atelectasis, hilar enlargement, or pleural effusion . At present, SPNs are a focus of research, primarily related to imaging, biomarkers, and histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Divisi et al [12] reported that solitary pulmonary nodules (SPNs) are incidentally found from 0.09 to 7% on chest imaging studies. The etiology of SPNs is broad and includes both benign (such as caused by infection, inflammation, or hemorrhage) and malignant disease (such as lung cancer and pulmonary metastases).…”
Section: Role Of 18f-fdg Pet-ct In Detection Of Extrahepatic Metastasismentioning
confidence: 99%